Genetic and Biochemical Evidence for the Involvement of α-1,4 Glucanotransferases in Amylopectin Synthesis - Colleoni, Christophe (American Society of Plant Physiologists, 1999)
We describe a novel mutation in the Chlamydomonas reinhardtii STA11 gene, which results in significantly reduced granular starch deposition and major modifications in amylopectin structure and granule shape. This defect simultaneously leads to the accumulation of linear malto-oligosaccharides. The sta11-1 mutation causes the absence of an α-1,4 glucanotransferase known as disproportionating enzyme (D-enzyme). D-enzyme activity was found to be correlated with the amount of wild-type allele doses in gene dosage experiments. All other enzymes involved in starch biosynthesis, including ADP-glucose pyrophosphorylase, debranching enzymes, soluble and granule-bound starch synthases, branching enzymes, phosphorylases, α-glucosidases (maltases), and amylases, were unaffected by the mutation. These data indicate that the D-enzyme is required for normal starch granule biogenesis in the monocellular alga C. reinhardtii.